Clinical Profile of Acute Coronary Syndrome in Rural Trivandrum - Roby, Anil; Abhilash, TP; Binu, SS; Noufal, A (Asian Journal of Medical Research, 2014)
Objective: To determine the clinical profile of acute coronary syndromes in rural Trivandrum Method: Retrospective study conducted at Sree Gokulam Medical College and Research Foundation, a teaching hospital in rural Trivandrum.Patients presenting with Acute Coronary Syndrome to the Coronary Care unit of this Hospital from July 2010 to Jan 2012 were included in the study. Patients were divided into ST segment elevation Myocardial Infarction (STEMI) and Non ST Segment elevation Myocardial Infarction/unstable angina (NSTEMI/UA) for the purpose of analysis. Results: 342 patients were admitted during the study period. 252(74%) were males and 90(26%) were females. 162 patients (47%) had STEMI and 180 patients (53%) had NSTEMI/UA. STEMI cases were reported more among males (52%),while NSTEMI/UA were seen more among females (68%). Hypertension was the major risk factor (54%) followed by Diabetes(50%) and Smoking (47%). Majority of the patients (39%) reached the hospital within 3-6 hours. Chest pain was the major presenting symptom (76%), followed by sweating (66%) and breathlessness (28%). Among STEMI cases, AWMI was more in females (45%) , while IWMI was more in males (45%). PCI was done in 44% of cases with STEMI, while in NSTEMI cases, conservative treatment was done in majority of cases. CABG was done in 3 males and 4 females with NSTEMI and 10 males and 8 females with STEMI. Total mortality was 8 %. Higher mortality rates were observed among females and also among patients with STEMI. Conclusion: CAD is an emerging epidemic in India. Males are commonly affected, though mortality is seen more among females. Even in rural areas, hypertension, Diabetes and Smoking were found to be major risk factors.